Analysis Of Symbolism In Robert Frost’s Poems - risma kartika dewi; Novi Sriwulandari; Adhiva Windy Astiti (Reforma : Jurnal Pendidikan dan Pembelajaran, 2023)
The researchers are interested in analyzing symbolism in poem. Symbolism usually used by the poet to hide the original meaning of his writing. Symbolism is also interpreted as a sentence that has a broader meaning than the explanation of the original sentence. In this study, the researchers focus to analyze the meaning of symbols in masterpieces of Robert Frost's poems. This study used descriptive qualitative method. Fifth masterpieces of Robert Frost’s Poems are On A The Rose Family, A Minor Bird, Stopping by Woods On a Snowy Evening, Fire and Ice, and Nothing Gold Can Stay. Those poems tell about human life that has many obstacles before it reaches the purpose of life he wants. In conclusion, the symbols are found in Masterpieces of Robert Frost's poems indicate almost same meaning or some theme that is a way of life that must be passed. In addition, Robert Frost's poems have a moral message relating to life and human.